Examining the Sexual Enigma of the Immigrant Paradox with International Students - Belcastro, Philip A.; Ramsaroop-Hansen, Hardaye (Journal of International Students, 2018)
The metamorphosis of core sexual practices and sexual orientation norms resulting from the acculturation of U.S. native and non-native residents remains an enigma. A convenience sample from a metropolitan community college was drawn to describe the consequences of acculturation on U.S. international students’ core sexual practices and sexual orientation. Findings include: (1) observed differences in male international student sexual practices to that of the native male population were attributed to social opportunity and not the immigrant paradox, and (2) female international students’ core sexual practices and sexual orientation shifted over time to the higher risk sexual practices of the native female population. The U.S. needs to commit resources including qualified health educators, to support state mandated public school and undergraduate sex education for U.S. juveniles and young adults.